Emerging concepts in photocatalytic organic synthesis - Susanne Reischauer; Bartholomäus Pieber (iScience, 2021)
Summary: Visible light photocatalysis has become a powerful tool in organic synthesis that uses photons as traceless, sustainable reagents. Most of the activities in the field focus on the development of new reactions via common photoredox cycles, but recently a number of exciting new concepts and strategies entered less charted territories. We survey approaches that enable the use of longer wavelengths and show that the wavelength and intensity of photons are import parameters that enable tuning of the reactivity of a photocatalyst to control or change the selectivity of chemical reactions. In addition, we discuss recent efforts to substitute strong reductants, such as elemental lithium and sodium, by light and technological advances in the field.